Reducing educational poverty and failure to study by observing educational justice in the education system of the Islamic Republic of Iran - Masoumi, Mahmoud; Mohammadi Naeini, Mozhgan; Faghihi, Alireza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Educational justice is the foundation of thought and culture in a society, forming a part of cultural justice, and facilitates individuals’ access to equal educational opportunities. The absence of educational justice slows the progress and development of human civilization and leads to the spread of class conflict, educational poverty, and school dropout. Therefore, this research compiles statistics on school dropouts and presents strategies to reduce poverty and dropout rates while maintaining educational justice. Methods: This research adopts a descriptive methodology and documentary analysis approach. Data have been collected by card-indexing from documentary sources such as articles, books, and credible domestic and international websites, as well as high-level documents including the Fundamental Transformation Document of Education and Training. Results: One of the essential indicators of justice-oriented policies is ensuring the opportunity for educational growth and equity for all people, regardless of gender, race, class, ethnicity, or color. Conclusion: The necessity of providing free and quality education and training for all individuals of school age is a fundamental concern referred to as educational justice. The existence of various challenges and obstacles in achieving this goal has led to inequalities and injustices.